Neurocriminology as an emerging applied discipline - Moya Albiol, Luis (2017)
Neurocriminology aims to apply neuroscience methodology and study  techniques  in  order to understand, predict, study and even predict delinquencyandcriminality.Neurocriminological knowledge could be used in violence prevention, diagnostic and treatment, and also in estimating the likelihood of recidivism. All this is not free of ethical and  legal  issues,  but  neuroscience is becoming an important influence when understanding and studying violent and criminal behaviour. Moreover, Positive Neurocriminology focus on the positive processes such as empathy, altruism, positive emotions and prosocial behaviour, among others. This knowledge could be used in the development of prevention and intervention delinquency programs.